The Structure of Short and Genomic DNA at the Interparticle Junctions of Cationic Nanoparticles. Issue 17 (7th August 2017) - Gisbert‐Quilis, Patricia; Masetti, Matteo; Morla‐Folch, Judit; Fitzgerald, Jamie M.; Pazos‐Perez, Nicolas; Garcia‐Rico, Eduardo; Giannini, Vincenzo; Alvarez‐Puebla, Ramon A.; Guerrini, Luca
Abstract : Current understanding of the mechanisms underlying noncovalent interactions between native DNA and nanoparticles, as well as their impact on the double‐helix structure, is far from providing a comprehensive view. It is known that these interactions are largely defined by the physicochemical properties of the metal/liquid interface, in particular by the nanoparticle surface charge. Remarkably, while DNA unzipping upon binding with cationic nanoparticles is reported, the exact determinants of this structural perturbation remain unclear. Herein, plasmon‐based spectroscopies (surface‐enhanced Raman scattering (SERS) and surface‐plasmon resonance (SPR) and theoretical simulations are combined to directly investigate the role of the cooperative binding of cationic nanoparticles with different surface charges on the structural integrity of a large variety of DNAs. The intrinsic nature of the SERS effect unlocks the possibility of selectively examining the impact of nanoparticle clustering on the duplex structure over a wide degree of colloidal aggregation and without the need of external intercalating dyes or strand labeling. This extensive work provides new fundamental insights into the interaction between nucleic acids and nanoparticles, addressing key questions regarding the role played by multiple variables such as the nanoparticle surface charge, the DNA‐mediated cluster size and geometry, and nucleic acids' length, composition, and conformational properties. Abstract : Unraveling the mechanism of DNA unzipping mediated by interaction with cationic nanoparticles. Key questions regarding the cooperative role of nanoparticle clustering, nanoparticle surface charge, and nucleic acids properties are directly addressed by combining plasmon‐based spectroscopies and theoretical simulations with no need of external intercalating dyes or prelabeling steps.